A 4NsL chromosome segment from Leymus mollis confers stripe rust and Fusarium head blight resistance in wheat - Du, Xin; Jin, Yanlong; Ren, Wei; Ge, Dongdong; Xu, Xiaomin; Zhao, Xiaoqi; Wang, Yanzhen; Li, Tingting; Zhao, Jixin; Wang, Changyou; Li, Tingdong; Chen, Chunhuan; et al. (Frontiers in Plant Science, 2025)
Leymus mollis (Trin.) Pilg. (2n = 4x = 28, NsNsXmXm) serves as a tertiary genetic pool for wheat improvement, harboring valuable traits such as disease resistance and stress tolerance. To harness this potential, we characterized two novel wheat-L. mollis translocation lines, M892 and M956, derived from a cross between common wheat and a 4Ns disomic addition line. Phenotypic evaluation revealed that M956 displays high resistance to both stripe rust and Fusarium head blight, while M892 is susceptible; both lines exhibit enhanced grain weight, with M892 additionally showing a dwarf phenotype. Cytogenetic analyses identified M892 as a T5DL-4NsL-5DL·5DS insertional translocation line and M956 as a T4NsL-5DL·5DS terminal translocation line. Genetic mapping localized the stripe rust resistance to a critical 98 Mb region on chromosome 4NsL, and comparative transcriptomics pinpointed 47 candidate resistance genes uniquely upregulated in M956. Furthermore, we developed eight 4NsL-specific molecular markers, providing a practical tool for the marker-assisted utilization of these resistance genes in wheat breeding programs.